An Analysis of The Role of Digital Marketing in Shaping Consumer Purchasing Decisions in MSMEs In the Digital ERA - Simon, Sharren Christya; Ningrum, Annisa Cahya; Luiskiy. S, Angellica Monica; Suwito, Marco Hubertus; Mulyandi, M. Rachman (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This study aims to analyze the role of digital marketing in shaping consumer purchasing decisions among MSMEs in the digital era through a literature review approach. The method used involves examining various scientific journals and relevant academic publications from 2024 - 2025 that discuss the relationship between digital marketing strategies and consumer purchasing behavior. The findings indicate that digital marketing does not only function as a promotional medium but has evolved into a strategic communication system that influences consumers’ perceptions, trust, and emotional attachment toward MSME products. Key factors proven to influence purchasing decisions include digital content quality, the level of digital trust, electronic word of mouth (eWOM), and the intensity of interaction between MSME actors and consumers on digital platforms.